2022
DOI: 10.7759/cureus.31264
|View full text |Cite
|
Sign up to set email alerts
|

A Histopathological Study of Endometrial Biopsy Samples in Abnormal Uterine Bleeding

Abstract: Background: Abnormal uterine bleeding (AUB) is the most common health issue in women, defined as any bleeding pattern that differs in frequency, duration, and amount. Endometrial sampling and its histopathological examination is the first-line test in patients presenting with AUB. The aim of this study was to analyze the histopathological patterns of endometrium in women with AUB and to find the predominant histopathologic pattern in the different age groups of women with AUB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 14 publications
4
4
0
Order By: Relevance
“…Secretory endometrium incidence in our study was 25.5%. In the literature, similar incidences of secretory endometrium were found at 18% [7].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Secretory endometrium incidence in our study was 25.5%. In the literature, similar incidences of secretory endometrium were found at 18% [7].…”
Section: Discussionsupporting
confidence: 64%
“…In our study, the most common symptom of abnormal uterine bleeding was menorrhagia found in 91.5% of patients. Menorrhagia is the most common complaint in the younger age group and the perimenopausal age group, both in our study and in the literature [ 7 ]. A total of 43 patients (8.5%) have undergone endometrial sampling due to postmenopausal bleeding.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Time-lapse microscopy is the most effective approach. 116,117 In contrast, fixed cells labeled with fluorescent antibodies are preferred for mapping proteins difficult to tag or express or for analyzing the static localization of multiple proteins in the cell. 57 However, both methods can be used for comparative studies to detect one protein in different cell types under varying test conditions.…”
Section: Imaging Methodsmentioning
confidence: 99%
“…To observe organellar protein movement, it is crucial to maintain cell viability by ensuring optimal temperature and CO 2 levels. Time-lapse microscopy is the most effective approach. , In contrast, fixed cells labeled with fluorescent antibodies are preferred for mapping proteins difficult to tag or express or for analyzing the static localization of multiple proteins in the cell . However, both methods can be used for comparative studies to detect one protein in different cell types under varying test conditions. Staining concentration, incubation time, and imaging interval/frequency should be determined empirically to minimize cytotoxicity and maintain cellular function (Figure ).…”
Section: Subcellular Proteomics Methodsmentioning
confidence: 99%